Time series of bed shear stress in the cross section of the seeding locations of bedload tracers in an alpine section of the Drava River between 11 May 2018 and 11 June 2018 - Klösch, Mario; Pessenlehner, Sebastian; Gmeiner, Philipp; Habersack, Helmut (In: Klösch, M et al. (2024): Data set from a bedload tracer field study in an alpine section of the Drava River in 2017 and 2018 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.969734, 2024)
This is a data set related to a bedload tracer field study in an alpine section of the Drava River between 11 May 2017 and 11 June 2018. A time series of bed shear stress is provided for the seeding site of the tracers in the time span of the entire tracer study. The shear stress was calculated from water depths that were modelled with a one-dimensional hydrodynamic-numerical model and based on a channel slope obtained from the analysis of cross-sections. The shear stress can also be calculated for cross-sections downstream of the seeding location by using the functions available in the corresponding publication.
Keywords: Active VHF transmitters; Bedload tracers; Bedload velocity; Drava River; Gravel-bed River; Gravel mobility; Tracer slowdown